2002
DOI: 10.1002/jat.847
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the TNP‐OVA and direct popliteal lymph node assays for the detection of immunostimulation by drugs associated with anaphylaxis in humans

Abstract: Using current animal models, it is not possible to identify low-molecular-weight compounds (LMWCs) that are likely to be associated with anaphylaxis. It is generally accepted that the ultimate effector mechanism involves drug-induced IgE antibody. The objective of the present study was to determine if diclofenac, zomepirac and glafenine, which are associated with anaphylaxis in humans, have immunostimulating potential in the murine TNP-OVA (trinitrophenyl-ovalbumin) popliteal lymph node assay (PLNA), and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…We and others have previously shown that up-regulation of costimulatory signals, collectively representing signal 2, is a key process in drug-induced immune responses (Pieters & Albers 1999;Pirmohamed et al 2002;Seguin & Uetrecht 2003;Kaplowitz 2005;Nierkens et al 2005a, b;Uetrecht 2008). To demonstrate the capacity of a drug to provide co-stimulatory adjuvant signals, the potential to stimulate adaptive immune responses to unrelated bystander antigens, such as trinitrophenyl-ovalbumin (TNP-OVA), can be determined (Albers et al 1997;Gutting et al 1999Gutting et al , 2002Nierkens et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that up-regulation of costimulatory signals, collectively representing signal 2, is a key process in drug-induced immune responses (Pieters & Albers 1999;Pirmohamed et al 2002;Seguin & Uetrecht 2003;Kaplowitz 2005;Nierkens et al 2005a, b;Uetrecht 2008). To demonstrate the capacity of a drug to provide co-stimulatory adjuvant signals, the potential to stimulate adaptive immune responses to unrelated bystander antigens, such as trinitrophenyl-ovalbumin (TNP-OVA), can be determined (Albers et al 1997;Gutting et al 1999Gutting et al , 2002Nierkens et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Streptozocin was shown to induce an IgG 2a or IgG 2b response with IFN-γ release due to stimulation of CD4 + T H1 cells, whereas diclofenac, zomepirac and glafenin induced an IgG 1 or IgE response due to T H2 stimulation and IL-4 release (Gutting et al, 2002a). Mercuric chloride as well as high doses of zomepirac and glafenin, however, produced a mixed IgG 1 , IgE, IgG 2a and IgG 2b response in this system (Albers et al, 1998;Gutting et al, 2002b).…”
Section: Modified Plnamentioning
confidence: 95%
“…The parameters used-PLN size, weight, cellularity, and lymphocyte proliferation-are indicative for immunostimulation. The introduction of reporter antigen (RA) additionally makes it possible to differentiate between sensitizing drugs, nonsensitizing drugs with adjuvant activity, and "innocent" drugs (drugs with no detectable immunomodulatory activity; Albers et al, 1997;Gutting et al, 1999Gutting et al, , 2002 by means of the specific immunological requirements for obtaining an IgG antibody response to the RA.…”
Section: Background Informationmentioning
confidence: 99%
“…In summary, the specific requirements for obtaining an IgG antibody response to TNP-OVA or TNP-Ficoll make it possible to differentiate between sensitizing chemicals, chemicals that are nonsensitizing but which possess adjuvant activity, and innocent chemicals (Albers et al, 1997;Gutting et al, 1999Gutting et al, , 2002.…”
Section: Background Informationmentioning
confidence: 99%